A Surgically Treated Case of Ureterovesical Amyloidosis of the Bladder in a Patient with Idiopathic Thrombocytopenia. (6th September 2018) - Kim, Sung Han; Park, Weon Seo; Joung, Jae Young; Lee, Kang Hyun; Chung, Jinsoo; Seo, Ho Kyung
Abstract : Idiopathic thrombocytopenia (ITP) is a bleeding disorder involving the destruction of platelets by the immune system. Systemic amyloidosis is another bleeding disorder involving amyloid deposits that create defects in coagulation and increased prothrombin and thrombin times. We report a 52-year-old man with ITP and new two-month-duration, painless gross hematuria without clot formation resulting in amyloidosis involving the ureterovesical area of the bladder. He had osteopenia, hypertension, and moderate thrombocytopenia due to ITP diagnosed 7 years previously. Cystoscopic examination with urine cytology and computed tomography imaging detected a 2-cm protruding solid bladder mass involving the left ureteral orifice and trigone and left mild hydroureteronephrosis, suggesting bladder cancer. Transurethral resection of the bladder mass was performed to confirm amyloidosis involvement in the ureterovesical junction of the bladder and ureter. Four weeks postoperatively, intermittent gross hematuria remained; hence, left ureteroneocystostomy was performed. Regular follow-up showed no signs of hematuria or intravesical recurrences for 14 months.